Evidence of unrestrained beta-cell proliferation and neogenesis in a patient with hyperinsulinemic hypoglycemia after gastric bypass surgery. Issue 6 (2nd November 2018) - Dadheech, Nidheesh; Garrel, Dominique; Buteau, Jean
ABSTRACT: Hyperinsulinemic hypoglycemia syndrome (HIHG) is a rare complication of roux-en-Y gastric bypass surgery. The pathology is associated with an excessive function of pancreatic beta-cells, and requires pancreas resection in patients that are recalcitrant to nutritional and pharmacological interventions. The exact prevalence is not clearly understood and the underlying mechanisms not yet fully characterized. We herein sought to perform histological and molecular examination of pancreatic sections obtained from a patient who developed HIHG as a complication of gastric bypass compared to 3 weight-matched controls. We studied markers of cellular replication and beta-cell differentiation by immunohistochemistry and immunofluorescence. HIHG after gastric bypass was characterized by a profound increase in beta-cell mass. Cellular proliferation was increased in islets and ducts compared to controls, suggesting unrestrained proliferation in HIHG. We also detected beta-cell differentiation markers in duct cells and occasional duct cells displaying both insulin and glucagon immunoreactivity. These histological observations suggest that beta-cell differentiation from ductal progenitor cells could also underly beta-cell mass expansion in HIHG. Altogether, our results can be construed to demonstrate that HIHG after gastric bypass is characterized by abnormal beta-cell mass expansion, resulting from both unrestrained beta-cell replication and neogenesis.